Xenoma-like formations induced by Soricimyxum fegati (Myxosporea) in three species of shrews (Soricomorpha: Soricidae), including records of new hosts - Dyková, Iva; Tyml, Tomáš; Kostka, Martin (Folia parasitologica, 2011)
In South Bohemia, Czech Republic, 178 shrews, including 98 common shrews, Sorex araneus L., 70 pygmy shrews, Sorex minutus L., and 10 lesser white-toothed shrews, Crocidura suaveolens (Pallas), were examined for Soricimyxum fegati Prunescu, Prunescu, Pucek et Lom, 2007 infections, using squash preparations of unfixed tissues, histological sections and molecular methods. The infection was found in 51 (52%) S. araneus, 14 (20%) S. minutus and 1 (10%) C. suaveolens. The records of the latter two species extend host range of S. fegati. Lesions associated with S. fegati infections in the liver, the organ of specific localisation of the parasite, were found to be induced by proliferative stages migrating toward lumina of bile ducts. In other organs of these three host species, xenoma-like formations (XLFs) were found that severely injured blood vessels. XLFs contained presporogonic stages of S. fegati, whose species identity was evidenced using molecular methods.
Keywords: Host Specificity; Myxozoa; játra; Bile Ducts; cévy; Blood Vessels; sekvence nukleotidů; druhová specificita; Shrews; Sequence Analysis, DNA; Molecular Sequence Data; Parasitic Diseases, Animal; molekulární sekvence - údaje; Organ Specificity; parazitární nemoci u zvířat; zvířata; žlučové cesty; hostitelská specificita; sekvenční analýza DNA; RNA ribozomální; Liver; Base Sequence; RNA, Ribosomal; Czech Republic; Species Specificity; Animals; Česká republika; orgánová specificita; rejskovití